The Flagrance of the Sacred. Notes on the Miraculous Event in Ordet by Carl Theodor Dreyer - Tonion Fabio Pezzetti (Acta Universitatis Sapientiae: Film and Media Studies, 2022)
Can the transcendence of the sacred be represented through the potential of cinema, a medium based on the ontological reproduction of the Real? Can the dimension of the completely Other, whose limits and boundaries are hardly identifiable, come to the screen and become sensitive and perceptible? This contribution, taking as references the phenomenological dimension of the sacred proper to the investigation of Father Amédée Ayfre and the more stylistic one studied by Paul Schrader, intends to propose a reflection on how the miraculous event, understood as an objective suspension of physical laws, of narrative verisimilitude, in which the procedures of representation and rendering in images are configured as a fracture with respect to the customary nature of aesthetic expression of reality, are made evident in Carl Theodor Dreyer’s Ordet.